Removal of Indium Ions from Aqueous Solutions Using Hydroxyapatite and Its Two Modifications - Inga Zinicovscaia; Nikita Yushin; Doina Humelnicu; Maria Ignat; Ionel Humelnicu; Dmitrii Grozdov; Tatyana Vershinina (Separations, 2023)
Hydroxyapatite (HAP) coupled with its two modifications HAP P123 and HAP F127 were applied for indium removal from aqueous solutions. Adsorbents’ abilities to remove indium ions were assessed in relation to pH, time of contact, indium concentration, temperature, and presence of co-existing ions. Adsorption was discovered to be pH-dependent for all sorbents, with maximum indium ion removal at pH 4.0. Both the Langmuir and the Freundlich isotherm models were used to explain the experimental results. For all adsorbents, the Freundlich isotherm provided a better description of the equilibrium of the sorption. The sorption capacity computed from the Langmuir model changed from 10,799 mg/g for HAP F127 to 11071 mg/g for HAP. A number of models were used to describe the adsorption’s kinetics. The adsorption of indium on HAP was better described by the pseudo-second-order model, on HAP P123 by the pseudo-first-order model, and on HAP F127 by the Elovich model. Thermodynamic parameters showed that indium ions’ adsorption onto HAP adsorbents was a feasible, spontaneous, and exothermic process. The effectiveness of indium removal by the examined adsorbents was unaffected by the presence of other metal ions in the solutions. ORCA quantum chemistry software was used to theoretically examine the interactions between the surfaces of adsorbents and the indium ions. High desorption efficiency showed that the applied adsorbents can be used for manifold wastewater treatment.